Direito à saúde do idoso portador de doença renal crônica: uma análise no município de Castanhal-Pará - PINTO, Cleidiane Martins (Universidade Federal do Pará, 2018)
This research is about health law as a basic human right of all human beings, a right that can’t be excluded from the elderly, who are even in more need of this due to their biological condition, which will imply more investments and expenses made by the government with the goal to provide sanity for everyone but especially forthe old aged population. The essay exposes the liberalism of principles as theoretical models that are capable of substantiate the government’s duty of providing this human right (health law) to every citizen, based on John’s Rawls theory of distributive justice. By the same token, bioethical principles were stated as vectors to settle the emblematic cases, giving the chance of an equal health service especially for the elderly. It’s an exploratory descriptive research, with qualitative approach, for the old aged population that suffer chronic kidney disease and that need health hedge from the “Sistema Único de Saúde” for hemodialysis treatments. Field researches were made with social information and real diagnostics of those who suffer chronic kidney disease; biographical research through scientific perusal, with the aim to understand the concepts explained in this research; also, official government documents were analyzed; legal processes; and the applicable legislation. Through the methodological process, we can see that Brazil’s government, even though it has a constitutional regulation that cares about the distributive justice, when it’s needed; there are limitations for the defrayal in the public sanity, leaving uncovered the majority of the social welfare, for example the long waiting lists for those who need hemodialysis treatment, which is bigger everyday.